High Load With Lower Repetitions vs. Low Load With Higher Repetitions: The Impact on Asymmetry in Weight Distribution During Deadlifting - Whittal, Mitchel C.; Zwambag, Derek P.; Vanderheyden, Luke W.; McKie, Greg L.; Hazell, Tom J.; Gregory, Diane E. (Frontiers in Sports and Active Living, 2020)
This study investigated weight distribution between the lower limbs using a symmetry index (SI) score of the vertical ground reaction forces (GRF) and measures of postural stability in high load/low repetition (termed “heavy”) and low load/high repetition (termed “light”) deadlifting. Ten participants performed two deadlift protocols with equal cumulative external load. These protocols were designed to represent standard high load/low repetition and low load/high repetition workouts; order was random and separated by 7 days. An effect of lifting condition (p = 0.023) and set number (p = 0.011) was observed such that lifts in the heavy condition were less symmetrical than those in the light condition and lifts became more symmetrical as set number increased. There was no effect of lift number on symmetry of force production (p = 0.127). Additional analysis revealed that center of pressure (COP) path length was greater during heavy lifts (p = 0.002) however COP range was unaffected suggesting controlled point of force application within the same boundaries regardless of lifting condition. As asymmetries have been previously associated with increased injury risk, greater training emphasis on the symmetrical performance of sub-maximal deadlifts should be considered to try to minimize the development of asymmetries.